(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the characteristics of the activities of physical education and sports specialists, the proposed model and principles of continuing education. Selection and recruitment of personnel in the field of physical education and sports, ensuring high efficiency of the system. Aimed at ensuring the continuity of the process of training specialists in the field of physical education and sports and improving the professional development of specialists.